Antioviposition and Reduction of Callosobruchus chinensis Pic. 1902 (Coleoptera: Bruchidae) Emergence on Phaseolus vulgaris by Dioscorea sansibarensis Powder and Its Chemical Composition - Godfrey O. Mauti; Peter F. Kasigwa; Justus M. Onguso (Psyche: A Journal of Entomology)
Callosobruchus chinensis causes damage to the Phaseolus vulgaris seeds. Traditionally, Dioscorea sansibarensis serves as a medicinal plant. Naturally, D. sansibarensis has toxins that protect against herbivores and the surrounding invasive plants in its natural habitat. Phytochemical analysis by thin-layer chromatography (TLC) and laboratory experiments was carried out to determine the activity of D. sansibarensis leaves, bulbils, and yams powders on antioviposition and inhibition of the F1 emergence of C. chinensis. Bioassay data were subjected to nonparametric (Kolmogorov–Smirnov) statistical analysis and a generalized linear model at P≤0.05. Statistically, the powders had an antioviposition activity of 34.3% (R2 = 0.343). A recommendable activity on antioviposition was displayed by the yams powder; treatment by 0.8 g of yams powder had a Wald Chi-Square value of 1.291, P=0.26. Inhibition of F1 emergence was significantly attained by the yams powder; the treatment by 0.6 g of yams powder had a Wald Chi-Square value of 7.72, P=0.01. Statistically, the bulbils powder displayed low antioviposition and inhibition of F1 emergence. Observations on the TLC exposed compounds with similar Rf values; saponin with an Rf value of 0.72 was portrayed in the leaves, bulbils, and yams. A terpenoid and a flavonoid with Rf values of 0.37 and 0.71, respectively, were observed in bulbils and yams but absent in leaves. A terpenoid with an Rf value of 0.49 was visualized in leaves and bulbils but not in the yams powder. The study concluded that the D. sansibarensis yams and leaves powders are viable for application by the farmers in the protection of stored legumes against attack by C. chinensis. However, there may be other diverse interests in other storage insects and other methods of phytochemical analysis that have not been investigated.